Metaphors of Entrepreneurship among Polish Students: Preliminary Research Findings - Michał‚ Chmielecki; Łukasz Sułkowski (Entrepreneurial Business and Economics Review, 2016)
Objective: In Poland entrepreneurship is often perceived as an extremely risky process and entrepreneurs are often portrayed in a negative light. The research goals of our exploratory study is to identify the entrepreneurship metaphors among Polish management students.